Acceptance of near-natural greenspace management relates to ecological and socio-cultural assigned values among European urbanites - Lampinen, Jussi; Tuomi, Maria; Fischer, Leonie K.; Neuenkamp, Lena; Alday, Josu G.; Bucharova, Anna; Cancellieri, Laura; Casado-Arzuaga, Izaskun; Čeplová, Natálie; Cerveró, Lluïsa; Deák, Balázs; Eriksson, Ove; et al. (Basic and applied ecology, 2021)
Grasslands are widespread elements of urban greenspace providing recreational, psychological and aesthetic benefits to city residents. Two urban grassland types of contrasting management dominate urban greenspaces: frequently mown, species-poor short-cut lawns and less intensively managed, near-natural tall-grass meadows. The higher conservation value of tall-grass meadows makes management interventions such as converting short-cut lawns into tall-grass meadows a promising tool for urban biodiversity conservation. The societal success of such interventions, however, depends on identifying the values urban residents assign to different types of urban grasslands, and how these values translate to attitudes towards greenspace management. Using 2027 questionnaires across 19 European cities, we identify the assigned values that correlate with people's personal greenspace use and their preferences for different types of urban grasslands to determine how these values relate to the agreement with a scenario of converting 50% of their cities’ short-cut lawns into tall-grass meadows. We found that most people assigned nature-related values, such as wildness, to tall-grass meadows and utility-related values, such as recreation, to short-cut lawns. Positive value associations of wildness and species richness with tall-grass meadows, and social and nature-related greenspace activities, positively correlated with agreeing to convert short-cut lawns into tall-grass meadows. Conversely, disapproval of lawn conversion correlated with positive value associations of cleanliness and recreation potential with short-cut lawns. Here, people using greenspaces for nature-related activities were outstandingly positive about lawn conversion. The results show that the plurality of values assigned to different types of urban grasslands should be considered in urban greenspace planning. For example, tall-grass meadows could be managed to also accommodate the values associated with short-cut lawns, such as tidiness and recreation potential, to support their societal acceptance.